Tunable infrared laser absorption spectroscopy of aluminum monoxide A2Πi−X2Σ+. (March 2022) - Murzyn, C.M.; Allen, D.J.; Baca, A.N.; Ching, M.L.; Marinis, R.T.
Highlights: Absorption diagnostic capable of quantifying aluminum monoxide temperature and column density. Rotationally resolved optical absorption spectra of aluminum monoxide A 2 Π i − X 2 Σ + . First use of the AlO A 2 Π i − X 2 Σ + transition to characterize aluminum combustion. Abstract: We report the details of an infrared, laser absorption diagnostic capable of quantifying aluminum monoxide temperature and column density at 100 kHz repetition rate. This novel technique employs a near infrared MEMS-VCSEL to measure rotationally resolved optical absorption spectra of aluminum monoxide A 2 Π i − X 2 Σ + from approximately 7400 –7900 cm − 1 . Temperatures and column densities are extracted from model regressions to provide temporally resolved thermochemical information on aluminum oxidation reactions. The measurement capability is demonstrated by performing 100 kHz measurement in the plume of an exploding bridgewire with measured temperatures of 3450–3100 K and column densities of 1– 11 × 10 16 cm − 2 . To the authors knowledge, this is the first use of the AlO A 2 Π i − X 2 Σ + transition to characterize aluminum combustion environments. Details regarding signal extraction and calibration of MEMS-VCSEL spectra are also included. Although unsuccessful, efforts to extract kinetic temperature and column density from simultaneously measured, atomic aluminum 2 P 3 / 2, 1 / 2 − 2 S 1 / 2 transitions at 7618 cm − 1 and 7602 cm − 1 are also described.